Frequency of Hyperthyroidism among Patients with Congestive Heart Failure Presenting at Tertiary Care Hospital, Peshawar - Din, Noor; Latif, Abdul; Rahman, Atif Ur; Ali, Sajjad; Parvez, Muzdalfa (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the frequency of hyperthyroidism among patients with congestive heart failure presenting at tertiary care hospital, Peshawar. Design of the Study: The study design was descriptive cross sectional. Study Settings: The study was conducted at Cardiology Department, Khyber Teaching Hospital, Peshawar from 18 Sept, 2019 to 18 Mar, 2020. Material and Methods: 5cc of venous blood was taken and sent to hospital laboratory for screening of the hyperthyroidism. All the laboratory investigations were carried out by single experience pathologist having minimum of five years of experience. Results of the Study: As per frequencies and percentages for hyperthyroidism, only 08 (4%) patient presented with CHF were recorded with hyperthyroidism Conclusion: In my study I have come to this conclusion that hyperthyroidism can cause high cardiac output and left ventricular hypertrophy, therefore, early and effective treatment of hyperthyroidism is highly recommended in preventing thyrotoxic cardiomyopathy.